Design and development of a low-cost, eco-friendly forklift for sustainable logistics management - Jalal, Asif; Farooq, Muhammad; Anwer, Izza; Hayat, Nasir; Munir, Adeel; Zahid, Imran; Akbar, Noreen Sher; Hamza, M.; Nouman, M.; Riaz, Fahid (Frontiers in Built Environment, 2025)
The U.S. Occupational Safety and Health Administration’s (OSHA) most recent estimates show that between 35,000 and 62,000 injuries occur every year due to forklift-related accidents. According to the National Safety Council (NSC) data, approximately 78 fatalities are reported every year. Moreover, manual loading and unloading of heavy items is time-consuming and poses significant risks to workers in small and crowded warehouses. To address these safety and efficiency concerns cost-effectively, an automated robotic forklift prototype was developed. The key features of this industrial robot include full rotational mobility with a zero-degree turning radius, which reduces the time and space required to turn around corners. It can be operated remotely via a mobile phone using Bluetooth or wi-fi. The motion control system, based on the ESP-32 microcontroller, significantly enhances its operational efficiency compared to manual operation. This study evaluates the performance of the robotic forklift prototype, cost-effectiveness, with loading and unloading capabilities as effective solutions to the challenges faced by workers. Additionally, structural analysis using Ansys confirmed that the design can safely withstand forces 60% greater than the intended design load of 50 N. Furthermore, the maximum stress experienced by the fork is 67% below the material yield strength, further demonstrating robustness and reliability. The integration of advanced technology and Eco-friendly design positions this forklift as a viable and sustainable option for improving material handling in various industrial sectors.